2022
DOI: 10.3390/ijms232415578
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Stem Cells Damaged by Deoxycholic Acid via AHR Pathway Contributes to Mucosal Barrier Dysfunction in High-Fat Feeding Mice

Abstract: High-fat exposure leads to impaired intestinal barrier function by disrupting the function of intestinal stem cells (ISCs); however, the exact mechanism of this phenomenon is still not known. We hypothesize that high concentrations of deoxycholic acid (DCA) in response to a high-fat diet (HFD) affect aryl hydrocarbon receptor (AHR) signalling in ISCs and the intestinal barrier. For this purpose, C57BL/6J mice feeding on a low-fat diet (LFD), an HFD, an HFD with the bile acid binder cholestyramine, and a LFD wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The bile acids, such as DCA mentioned above, are precisely secondary bile acids, which suggests that the digestion and utilization process of high-fat diets altered the metabolic activity of intestinal microbiota, reflected by similar results in humans [87,88]. A study in mice demonstrated that high-fat diets induced an increase in fecal DCA content and low-fat diets decreased the total BA content [89]. They also found that DCA disrupts intestinal mucosal barrier function by interfering with aryl hydrocarbon receptor (AHR) signaling in intestinal stem cells.…”
Section: Discussionmentioning
confidence: 74%
“…The bile acids, such as DCA mentioned above, are precisely secondary bile acids, which suggests that the digestion and utilization process of high-fat diets altered the metabolic activity of intestinal microbiota, reflected by similar results in humans [87,88]. A study in mice demonstrated that high-fat diets induced an increase in fecal DCA content and low-fat diets decreased the total BA content [89]. They also found that DCA disrupts intestinal mucosal barrier function by interfering with aryl hydrocarbon receptor (AHR) signaling in intestinal stem cells.…”
Section: Discussionmentioning
confidence: 74%
“…For example, a study using a mouse model reported that activation of AhR signaling promotes goblet cell differentiation and enhances MUC2 expression 25 . Furthermore, a high-fat diet decreases AhR signaling, which decreases MUC2 expression 26 . Regarding Nrf2, a study using low molecular seleno-aminopolysaccharide (LSA), which increases goblet cells and mucus, reported that LSA downregulates Keap1 expression and upregulates Nrf2 expression, thereby reducing abnormal changes in MUC2 and increasing the mucus layer in the intestine 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that reduced numbers of some intestinal epithelial cell types, such as goblet cells, Paneth cells (PCs) and intestinal stem cells (ISCs), may lead to disruption of the intestinal barrier function and damage epithelium homeostasis [22,23] . We next investigated the status of the goblet cells and the expression of MUC2 in SI.…”
Section: Improved Intestinal Morphology and Enhanced Mucin 2 (Muc2) S...mentioning
confidence: 99%